CARICOM Multi-Agency Health Family Life Education Project: Summary Report of Trinidad and Tobago Needs Assessment Study (Students 7-9 Years Old) - The University of the West Indies, Cave Hill, School of Education (School of Education, UWI, 1997)
The HFLE Needs Assessment Study was carried out to obtain data on student knowledge and views about health lifestyles, a range of psycho-social issues affecting youth, and some aspects of the modus-operandi of the existing HFLE curriculum. It also sought to explore the problems, concerns, and values of young people; possible goals, outcomes and teaching and assessment methods of HFLE; and factors affecting the teaching of HFLE. The intended respondents were students in primary and secondary schools, and their teachers, principals and parents. This report summarizes and discusses the responses of Trinidadian primary schools students 7-9 years old. These responses suggested that the students were quite aware of what are generally regarded as “good” foods, even though their own preferences were often in the direction of “junk” foods. The order of choice suggested that health-related topics were more popular than those involving interpersonal relationships. The main need was for assistance with homework. Many also required help with talking to parents, suggesting that there is a serious problem with family relationships supportive to education.
CARICOM Multi-Agency Health Family Life Education Project
Keywords: health and family life education; HFLE; needs assessment